Value Creation through Engineering Excellence Building Global Network Capabilities (Springer International Publishing, 2018)
This book provides a systematic framework for effectively creating value through engineering in global business networks, and contributes to an increasingly important branch of engineering operations. By updating the traditional disciplines of engineering and operations management and addressing challenges and opportunities in building global network capabilities, this study offers a contemporary guide for developing effective industrial policies to enhance the global competitiveness of engineering sectors, which will be extremely useful to engineering companies and policy-makers. Themes discussed include main trends and driving forces, state-of-the-art knowledge in relevant subject areas, new technologies and leading practice. This timely book will help researchers, managers and students to gain an overall understanding of the pioneering research occurring in this field and it will enable companies to benefit from global engineering networks.